Transperitoneal Laparoscopic Pyelolithotomy versus Percutaneous Nephrolithotomy for Treating the Patients with Staghorn Kidney Stones: A Randomized Clinical Trial - Soltani, Mohammad Hossein; Hossein Kashi, Amir; Farshid, Saman; Mantegy, Seyyed Javad; Valizadeh, Rohollah (Urology Journal, 2021)
Purpose: To compare the performance and outcomes of laparoscopic pyelolithotomy (LPL) versus percutaneous nephrolithotomy (PCNL) in the management of staghorn kidney stones. Materials and Methods: This study was a parallel-group randomized clinical trial study carried out on 68 patients with staghorn stones (one single piece or maximally two-piece stones with large extra renal part) over 18 years referred to Labbafinejhad Hospital. Patients were randomly divided on a ratio of 1:1 into two groups of LPL and PCNL using random allocation software. The primary outcome was the stone free rate, which was evaluated with KUB, and ultrasonography. Secondary outcomes were duration of surgery, bleeding, fever, post-operative pain, length of hospital stay, and postoperative complications. Results: The mean±SD age of patients in PCNL and LPL groups were 48.50 ± 13.33 years and 52.17 ± 15.74 years, respectively (P=.303). LPL was associated with a higher duration of surgery (196.55 ± 26.58 minutes versus 110.88 ± 34.82; P=.001). Hemoglobin drop in the PCNL group was higher than the LPL group (2.67 ± 2.61 g/dL versus -0.7912 ± 1.06 g/dL; P=.001). Stone free status was observed in 29 (85.3%) patients in the LPL group, which was significantly higher than the PCNL group (22 patients, 64.7%; P =.050). Conclusion: The results of this study indicate that LPL offers a higher stone free rate with less bleeding in patients with single particle or limited particles staghorn stones with extrarenal pelvis but is associated with a higher duration of operation. The application of LPL in patients with multiple stones carries a lower achievement and is not encouraged.